2016
DOI: 10.1371/journal.pone.0156882
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction of Consciousness Disorders in the Acute Stage Based on a Complementary Motor Behavioural Tool

Abstract: IntroductionAttaining an accurate diagnosis in the acute phase for severely brain-damaged patients presenting Disorders of Consciousness (DOC) is crucial for prognostic validity; such a diagnosis determines further medical management, in terms of therapeutic choices and end-of-life decisions. However, DOC evaluation based on validated scales, such as the Revised Coma Recovery Scale (CRS-R), can lead to an underestimation of consciousness and to frequent misdiagnoses particularly in cases of cognitive motor dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 45 publications
5
64
0
Order By: Relevance
“…In addition, the MBT‐r identified signs of residual cognition in 75% of patients who were classified as unconscious (coma/UWS) by the CRS‐R. Moreover, presence of residual cognition at an early stage was related to subsequent consciousness recovery, in agreement with previous findings with the first version of the MBT . Our data, prospectively obtained in an ICU setting, support the notion that a wide range of cognitive capacities might be detected early after brain injury, and, more important, that their assessment is critical for determining an accurate prognosis .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the MBT‐r identified signs of residual cognition in 75% of patients who were classified as unconscious (coma/UWS) by the CRS‐R. Moreover, presence of residual cognition at an early stage was related to subsequent consciousness recovery, in agreement with previous findings with the first version of the MBT . Our data, prospectively obtained in an ICU setting, support the notion that a wide range of cognitive capacities might be detected early after brain injury, and, more important, that their assessment is critical for determining an accurate prognosis .…”
Section: Discussionsupporting
confidence: 89%
“…In this respect, the validated scales used in the clinical evaluation of DOC are mainly based on residual motor output, therefore limiting their ability to unmask a patient's cognitive abilities to interact, in case of impaired motor efference/output. The Motor Behavior Tool (MBT) was developed as a complement to the Coma Recovery Scale‐Revised (CRS‐R), to identify subtle motor behavior not taken into account in the CRS‐R that could be useful to identify residual cognition in DOC patients. A previous preliminary study reported the usefulness of the MBT to predict outcome early after severe brain injury …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observation of spontaneous motor behaviors (that may or may not be intentional) could help diagnose covert consciousness, e.g. using analytical approaches such as the revised Motor Behavior Tool or subjective approaches based on caregivers' collective intelligence such as the ‘DoC feeling’ . The examiner should be mindful of confounding factors such as cranial nerve palsies, central and peripheral causes of quadriplegia, severe spasticity, hypokinesia and bradykinesia, and hypertonus or hypotonus .…”
Section: Resultsmentioning
confidence: 99%
“…First, using supplements to (corrections of) the behavioral scales might be viewed as a practically relevant initiative to overcome the limitations of the scales and increase diagnostic accuracy. The aforementioned learning test strategies and the complementary motor behavior evaluation tool recently described by Pignat et al (2016) could be interpreted as examples of those supplements/corrections (Di Perri et al 2016;Lancioni et al 2014a;Monti 2012). Second, repeating the assessment over time and using combinations of behavioral and electrophysiological or neuroimaging procedures for such an assessment would constitute important cautionary conditions to curb the risks connected with individual fluctuations and reduce misdiagnosis Dolce et al 2015;Gilutz et al 2015).…”
Section: Discussionmentioning
confidence: 99%